Marijuana medusa: The many pulmonary faces of marijuana inhalation in adolescent males. Issue 12 (23rd October 2018) - McGraw, Matthew D.; Houser, Grace H.; Galambos, Csaba; Wartchow, Eric P.; Stillwell, Paul C.; Weinman, Jason P.
Abstract: Marijuana use has risen dramatically over the past decade. Over this same time period, pediatric hospitals have seen an increase in presentation of adolescents with acute respiratory symptoms after recent marijuana inhalation. We report a case series of three adolescent males with significant findings of bilateral pulmonary nodules and ground glass opacities on chest imaging associated with recent marijuana inhalation. Lung biopsies in two of the three patients confirmed silica‐induced pneumoconiosis. The third patient was diagnosed with acute hypersensitivity pneumonitis without lung biopsy. Improvement in clinical symptoms and lung function testing were noted in two of three patients after marijuana inhalation cessation. This case series highlights the variety of severe pulmonary presentations in adolescents following recent marijuana inhalation. Future studies are required to assess whether these presenting pulmonary complications are from direct marijuana exposure or indirect associations with marijuana inhalation injuries.